PENYERTAAN MODAL USAHA UNTUK MEMBANTU PENINGKATAN KESEJAHTERAAN IBU KEPALA RUMAH TANGGA - Citra, Dewi Sriani; Gusrianto, Anindira Aiska; Melan, Firdania Desfani; Mundzir, Ilham; Warsito, Warsito (Universitas Muhammadiyah Tangerang, 2024)
Empowerment to the community is one of the important activities that must be carried out in the context of empowering efforts, especially in communities that are considered weak and vulnerable to poverty, so that they have the ability and strength to break away from adversity, backwardness, and backwardness. This empowerment activity for poor families aims to help a housewife who is trying to support her family, especially for her children. Although it is not easy to be a mother who also requires her to be the head of the household. In addition to having heavy burdens and dependents for his family. That way, this dhuafa family empowerment program focuses on efforts to provide business capital to Head of Household Mothers in the South Jakarta area. The method used in this empowerment is Youth Participatory Action Research (Y-PAR), which is used because of the collaboration between lecturers and students. This activity is also able to encourage families who play the role of Head of Household Mothers who were previously very limited in the economy but are now able to regain their economic resources in improving the welfare of their families.